Reflective Writing in the Competency-Based Curriculum at the Cleveland Clinic Lerner College of Medicine - Isaacson, J Harry (The Permanente Journal, 2008)
The Cleveland Clinic Lerner College of Medicine of Case Western Reserve University is a five-year medical school where the major emphasis is to train physician investigators. In this article we describe our experience with reflective writing in our competency-based medical school, which has reflective practice as one of the nine core competencies. We outline how we use reflective writing as a way to help students develop their reflective practice skills. Reflective writing opportunities, excerpts of student pieces, and faculty and student perspectives are included. We have experienced the value of reflective writing in medical school education and believe elements of our program can be adapted to other training environments.